U.S. Women's Intended Sources for Reproductive Health Care - Crissman, Halley P. (J Womens Health (Larchmt), 2016)
Introduction: The current sociopolitical climate and context of the Affordable Care Act have led some to question the future role of family planning clinics in reproductive health care. We explored where women plan to get their future contraception, pelvic exam/pap smears, and sexually transmitted infection testing, with a focus on the role of family planning clinics. Methods: Data were drawn from a study of United States adults conducted in January 2013 from a national online panel. We focused on English-literate women aged 18–45 years who answered items on intended sources of care (private office/health maintenance organization [HMO], family planning clinic, other, would not get care) for reproductive health services. We used Rao-Scott F tests to compare intended sources across sociodemographic groups, and logistic regression to model odds of intending to use family planning clinics. Probability weights were used to adjust for the complex sampling design. Results: The response rate was 61% (n = 2,182). Of the 723 respondents who met the inclusion criteria, approximately half intended to use private offices/HMOs. Among some subgroups, including less educated (less than high school), lower annual incomes (<$25,000) and uninsured women, the proportion intending to use family planning clinics was higher than the proportion intending to use private office/HMO in unadjusted analyses. Across all service types, unmarried and uninsured status were associated with intention to use family planning clinics in multivariable models. Conclusions: While many women intend to use private offices/HMOs for their reproductive health care, family planning clinics continue to play an important role, particularly for socially disadvantaged women.